Pengaruh Kompetensi Teknologi Informasi, Professional Judgement, dan Task Specific Knowledge terhadap Pendeteksian Fraud dengan Budaya Organisasi sebagai Pemoderasi - Nadya Annisa Nasruddin; Nurkholifah Burhanuddin; Nurul Emil Safitri (Universitas Muhammadiyah Palembang, 2025)
This study aims to examine the influence of information technology competence, professional judgment, and task-specific knowledge on fraud detection, as well as the role of organizational culture as a moderating variable. Data were collected through questionnaires completed by 103 internal auditors of PT Pegadaian in Makassar, Manado, Balikpapan, and Bali using purposive sampling. The analysis was conducted using partial least squares structural equation modeling (PLS-SEM). The results show that all three independent variables have a positive effect on fraud detection. Furthermore, organizational culture significantly moderates the relationship between information technology competence, professional judgment, and task-specific knowledge with fraud detection. These findings highlight the importance of internal auditors' competencies and the role of organizational culture in enhancing the effectiveness of fraud detection.